Volatile metabolites profiling to discriminate diseases of tomato fruits inoculated with three toxigenic fungal pathogens - 1Ibrahim,, A.D.; H., Hussaini,; Sani, A.; Aliero, A.A.; yakubu, S. E. (Research in Biotechnology, 2011)
The volatile metabolites of tomato fruits inoculated with three toxigenic fungi isolated from spoilt tomatoes were profiled using gas chromatography/mass spectrometry. Differences in the number and amount of volatile metabolites were observed. The study yielded a total of 52 different volatile metabolites. Healthy ripe tomato fruits yielded twenty-eight metabolites predominated among them were oleic acid amide (10.89%), 9-octadecenoic acid (9.83%), methyl cis-9-octadecenoate (7.73%), and the least was 2, 3-Heptanedione (0.32%). Tomato fruits inoculated with A. niger yielded 11; A. flavus yielded 15 different volatile metabolites while that inoculated with F. oxysporum yielded 8 volatile metabolites. Among them only 5 volatile metabolite occurred relatively consistent in fruits inoculated with A. niger and A. flavus while adogen 73 and 9-Octadecenoic acid (Z) occurred relatively consistently in fruits inoculated with the three fungi. Hexadecanoic acid and 6-Methyl-2,4-di - tert - butyl – phenol was common in fruits inoculated with F. oxysporum and A. niger with that of A. niger having the highest value (9.67%) for Hexadecanoic acid while fruits inoculated with F. oxysporum had highest (2.66%) for 6-Methyl-2,4-di - tert - butyl – phenol. Ten metabolites were unique to A. flavus while A. niger and F. oxysporum had 4 metabolites unique to each of them. This study suggests that these unique metabolites can be used as biomarkers to detect tomato diseases/pathogen or toxigenic fungi at an early stage of disease progression and to manage tomato diseases in storage and outbreak of food borne disease, after further validation under commercial conditions.